Faust, a tragedy. Part 1 - Goethe, Johann Wolfgang von 1749-1832.; Greenberg, Martin 1918 February 3-. (New Haven Yale University Press, 1992)
Faust is a classic of world literature, yet until now no English rendition of Goethe's philosophical and poetic drama has been able to capture its life, satire, irony, humor, and tragedy. Award-winning translator and critic Martin Greenberg here presents the first faithful, readable, and elegantly written version of Geothe's masterpiece available in English.
Pt. 1. Theil 1 -- pt. 2. Theil 2.
Includes bibliographical references (p. 153-156).
Translation of: Faust.
Keywords: Faust -- pproximately 1540 -- Drama